Perencanaan Rekrutmen Tenaga Pendidik Dalam Meningkatkan Mutu Lembaga Pendidikan Keagamaan Islam - Miftah Farid; Mulyawan Safwandy Nugraha (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2024)
One form of organizing non-formal education in Islamic religious education is Taman Pendidikan Al-Qur’an (TPQ). TPQ requires qualified ustadz and ustadzah to facilitate the educational process. Therefore, the management of ustadz and ustadzah is crucial for the institution and is included in the recruitment planning. This research was conducted at TPQ Darul Muzakkirin using a qualitative research approach. Data collection was carried out through interviews, observations, and documentation, analyzed using the Miles & Hubermas model, including data collection, data reduction, data presentation, and drawing conclusions. The results of this study revealed that the recruitment planning for ustadz and ustadzah at TPQ Darul Muzakkirin has been implemented in principle, although not yet supported by a fixed standard operating procedure. The recruitment planning conducted by TPQ Darul Muzakkirin is expected to serve as the foundation for the emergence of qualified ustadz and ustadzah, contributing to the quality improvement of TPQ Darul Muzakkirin through high-quality graduates as a form of quality educational output.